Can Incongruencies Between Prospective and Retrospective Ease-of-Use Perceptions Affect Post-Use Satisfaction Ratings?. (September 2014) - Sublette, M.A.; Carswell, C.M.; Seidelman, W.; Lee, M.; Kent, T.
Consumers' expectations about the usability of products may be an important contributor to their overall satisfaction with a design. The purpose of this study was to explore how incongruencies between predicted usability and actual usability of a design affect a user's post-use satisfaction ratings for a design. Participants predicted the usability of two stove designs and then used the designs to perform a task. Interactive stoves had varying degrees of burner-knob s-r compatibility. In general, the relative dissatisfaction associated with the "hard" design compared to the "easy" design was dependent on the initial usability prediction of the participant. Participants who initially predicted the design would be difficult-to-use had lower satisfaction ratings for easy-to-use designs than participants who initially predicted the same designs would be easy-to-use. These finding suggests that making a product look easy-to-use may be as important as actually making it easy-to-use, therefore designers should consider designing for both initial impressions of usability as well as actual usability.